The Miner Sentence Completion Scale: An Appraisal - Brief, Arthur P.; Aldag, Ramon J.; Chacko, Thomas I. (Academy of Management Journal, 1977)
Selected psychometric properties of the Miner Sentence Completion Scale (MSCS) were evaluated. In particular, the degree to which the MSCS converges with England's Personal Values Questionnaire (PVQ) was assessed, the convergent and discriminant validity of three MSCS subscales with three subscales of the Ghiselli Self-Description Inventory (SDI) was examined, and inter-scorer reliability for the MSCS was considered. No significant relationship between the MSCS and the PVQ was detected; limited evidence of convergent and discriminant validity between the MSCS and SDI was found; and questions were raised regarding the reliability of the procedures used for scoring the MSCS.